Layer-by-layer slot-die coated high-efficiency organic solar cells processed using twin boiling point solvents under ambient condition - Yang, Yu; Feng, Erming; Li, Hengyue; Shen, Zichao; Liu, Wanrong; Guo, Jingbo; Luo, Qun; Zhang, Jidong; Lu, Guanghao; Ma, Changqi; Yang, Junliang (Nano research, 2021)
Layer-by-layer (LbL) strategy has been developed to form bulk heterojunction (BHJ) structure for processing efficient organic solar cells (OSCs). Herein, LbL slot-die coating with twin boiling point solvents (TBPS) strategy was developed to fabricate highly efficient OSCs, which matches with large-scale, high throughput roll-to-roll (R2R) industrialized mass process. The TBPS strategy could produce high-quality thin film without any additive, leading to the optimized vertical phase separation with interpenetrating nanostructures, as well as the enhanced charge transport and extraction. Thus, the power conversion efficiency up to 14.42% was achieved for [(2,6-(4,8-bis(5-(2-ethylhexyl-3-fluoro)thiophen-2-yl)-benzo [1,2-b:4,5-b′]dithiophene))-alt-(5,5-(1′,3′-di-2-thienyl-5′,7′-bis(2-ethylhexyl)benzo[1′,2′-c:4′,5′-c′]dithiophene-4,8-dione)]:2,2′-((2Z,2′Z)-((12,13-bis(2-ethylhexyl)-3,9-diundecyl-12,13-dihydro-[1,2,5]thiadiazolo[3,4-e]thieno[2″,3″:4″,5″]thieno[2′,3′:4,5]pyrrolo[3,2-g]thieno[2′,3′:4,5]thieno[3,2-b]indole-2,10-diyl)bis(methanylylidene)) bis(5,6-difluoro-3-oxo-2,3-dihydro-1H-indene-2,1-diylidene))dimalononitrile (PM6:Y6) OSCs fabricated via sequentially LbL slot-die coating using the TBPS strategy under ambient condition. The research provides a potential route for industrialized production of high-efficiency and large-area OSC devices.